The Influence of Financial Literacy, Personal Income, And Education Level on The Financial Behavior of MSMEs in Malang Regency - Nur Faridatus Sholikhah; Sugeng Purwanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
MSMEs are pillars of the country's economy which play a role in creating markets, creating jobs and reducing poverty levels. As an MSME actor, good financial behaviour is very necessary because financial factors have a crucial role in determining business sustainability, which can be the main source of income for the most of MSME actor. Therefore, this research aims to see the influence of financial literacy, personal income, and education level on the financial behavior of MSME actors in Malang Regency. A total of 100 respondents were obtained in this research through distributing questionnaires. The research method is quantitative descriptive research with the used of a multiple linear regression method. The research showed that financial literacy and education level have a significant influence on the financial behavior of MSME actors in Malang Regency. Meanwhile, in this research it was found that personal income did not have a significant effect on the financial behavior of MSME actors in Malang Regency. Through this research, it can be concluded that financial literacy, personal income and education level have an influence of 53.7% on the financial behavior of MSME actors in Malang Regency. Meanwhile, the other 43.3% was influenced by various variables that were not in this study. This research delves into the human aspects driving these enterprises by examining three critical factors: financial literacy, personal income, and education level, providing a new perspective on the factors that influence financial behavior among MSME actors.